STRES KERJA DAN LINGKUNGAN KERJA SERTA PENGARUHNYA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA PADA PT. BPR LUHUR DAMAI KEDIRI TABANAN - PRAYANA, I KADEK WIRA DHARMA (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to empirically examine several things, including knowing and explaining the effect of work stress on work motivation, knowing and explaining the influence of the work environment on work motivation, knowing and explaining the effect of work stress on performance, knowing and explaining the influence of the work environment on performance, knowing and explaining the effect of work motivation on performance, and knowing and explaining the effects of work stress on performance through work motivation and knowing and explaining the influence of the work environment on performance through work motivation at PT. BPR Luhur Damai Kediri Tabanan. Respondents in this study were 68 employees of PT. BPR Luhur Damai Kediri Tabanan, collecting data in this study using sampling techniques using saturated samples (census research). Data analysis was performed using PLS (partial least square).The results showed that (1) Job stress has a positive and insignificant influence on employee work motivation, (2) The work environment has a positive and significant influence on employee work motivation, (3) Job stress has a negative and insignificant influence on employee performance, (4) The work environment has a positive and not significant influence on employee performance, (5) Work motivation has a positive and significant influence on employee performance (6) Job stress has a positive and significant effect on performance through employee work motivation, and (7) Environment work has a positive and significant influence on performance through employee motivation at BPR Luhur Damai Kediri Tabanan.